Quantifying firewood-transmitted forest pests at their source: an analysis of insects within a northern Colorado firewood processing facility - Snyder, Garron, author (Colorado State University. Libraries, 2024)
Urban and rural forests are subject to outbreaks from forest pests of native and foreign origin. Firewood is one of the primary dispersal agents of forest pests such as insects, bacteria, and fungi. However, few studies have attempted to quantify pest incidence within transported firewood. This study analyzed forest pest incidence within a firewood processing and holding facility in Northern Colorado by quantifying the proportions of pieces with galleries, live adult insects, dead adult insects, and larvae within imported and locally processed firewood. We also analyzed locally felled tree species for galleries, and adult or larvae species richness to investigate local incidence. Lastly, we utilized funnel traps baited with α-pinene-ethanol baits to capture and identify any species present within the property. Among the 3,250 pieces of firewood, 28% (925) contained galleries, less than 1% (12) had live insects, and zero contained larvae. The largest average proportion of galleries was observed in pine pallets (81% per pallet) and the smallest was observed in spruce (0.05% per pallet). In sampled logs, elm logs had the highest gallery incidence (90%), alive adult presence (80%), larvae presence (90%), and species richness. A variety of native, but potentially harmful pests were captured along with evidence of potentially harmful insects such as members of Buprestidiae, Cerambycidae, and Curculionidae. Based on our analysis, we suspect that the firewood tree species is an important factor to consider when quantifying and predicting forest pest dispersal. We also believe that local firewood is not inherently less likely to harbor potentially harmful species compared to imported firewood. Overall, better monitoring and regulatory structure will be necessary to prevent forest pest outbreaks.
Colorado State University Honors Program Fall 2024.
Fish and Wildlife Conservation Biology.
Forestry.
Keywords: firewood; forest pests; urban forests; emerald ash borer; dutch elm disease; elm bark beetle